Etno Parenting; Transformasi Buaian Anak-anak di Ogan Ilir Sumatera Selatan - Muharrahman Muhar; Amin Suyitno; Endang Rochmiatun; Zaimuddin; Ani Nafisah; Zaenal Abidin (Institut Agama Islam Negeri Madura, 2023)
This study aims to describe how the transformation of baby swings in Ogan Ilir, especially in Ridho Residence Indralaya Housing. The type of research used is ethnography with a qualitative descriptive approach. This study describes or explores information based on practical experience and ethnoparenting values. The transformation of the baby swing in the Ridho Residence Indralaya housing has undergone several changes, both in terms of shape and material, as well as changes from a more modern implementation aspect with the addition of various applications on the swing. Based on the findings in the field, there are still a few parents who use electric and electric swings because the prices are quite expensive. Meanwhile, the social status of parents at Ridho Residence Indralaya is still classified as lower middle class.